2016
DOI: 10.4172/2165-7556.1000165
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Occupational Contact Dermatitis

Abstract: This article reviews the scientific research concerning occupational contact dermatitis and the related methods of prevention. The information provided herein clarifies some difficulties involved in the confirmation of diagnoses and creating strategies for prevention. Occupational skin diseases, most of which are contact dermatitis arising from exposure to a culpable agent, constitute more than 35% of all work-related disorders. Contact dermatitis can be classified as either the irritant or the unfavorably all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…We found a significant relationship between personal hygene of workers and OICD. The results of this study support the results of previous research by Al-otaibi (2016) which concluded that poor personal hygene is one of the risk factors of OICD occurrence, so to decrease the incidence of OICD is suggested to improve personal hygene of workers; and Cahyawati & Budiono (2011) which conclude that personal hygene was correlated with dermatitis among fishermen. As previously mentioned by Callahan et al (2014), hand washing frequency (≥ 10 times a day) were associated with irritan hand dermatitis.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We found a significant relationship between personal hygene of workers and OICD. The results of this study support the results of previous research by Al-otaibi (2016) which concluded that poor personal hygene is one of the risk factors of OICD occurrence, so to decrease the incidence of OICD is suggested to improve personal hygene of workers; and Cahyawati & Budiono (2011) which conclude that personal hygene was correlated with dermatitis among fishermen. As previously mentioned by Callahan et al (2014), hand washing frequency (≥ 10 times a day) were associated with irritan hand dermatitis.…”
Section: Resultssupporting
confidence: 90%
“…Many inhibiting creams remove sticky oils and fats, thus reducing the need to wash with water and irritating soaps. The barrier cream should only be used on normal skin and not itch because it can aggravate dermatitis when used on inflamed skin (Al-otaibi, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact dermatitis can be caused by direct irritation from a substance, known as irritant contact dermatitis (ICD), or contact with an unfavorable allergen, known as allergic contact dermatitis (ACD). 3 Occupational contact dermatitis accounts for 90% of all work-related skin disorders. It can be divided into irritant contact dermatitis, which occurs in 80% of cases, and the rest are allergic contact dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Anthraquinones (AQ) represents an essential class of dyestuffs receiving worldwide attention due to their extensive range of applications in textile industry for colouring natural and synthetic fibers, [1][2] imaging devices, [3] foods, [4] paints, [5] cosmetics [6][7] and pharmaceutical industries. [8][9][10][11] They are widely reported to exhibit antitumor, [12][13] antiviral, [14][15] antifungal, [16] anti-laxative [17][18] and anti-inflammatory properties. [19][20] N-Aryl anthraquinone derivatives (Figure 1), have been exploited as a valuable tool for biochemical and pharmacological studies.…”
Section: Introductionmentioning
confidence: 99%